2011
DOI: 10.1002/cne.22719
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and experimental evidence supports the continuum of the central extended amygdala and a mutiple embryonic origin of its principal neurons

Abstract: The central extended amygdala is the major output center for telencephalic control of ingestion, fear responses, stress, and anxiety. In spite of the abundant data supporting the similarity in neurochemistry, connections, and function along the extended amygdala, embryological support for this continuum is lacking. By using a combination of in vitro migration assays, in situ hybridization, and immunostaining, here we show that its major components, including central amygdala and lateral bed nucleus of the stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
184
0
7

Year Published

2011
2011
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(204 citation statements)
references
References 94 publications
(206 reference statements)
13
184
0
7
Order By: Relevance
“…The projection neurons in the excitatory LA and BLA nuclei are derived from the VP and LP (Stenman et al, 2003;Puelles et al, 2000;Hirata et al, 2009). Neurons in the central and medial extended amygdala are originated from multiple telencephalic or extra-telencephalic progenitor zones (Bupesh et al, 2011a;Bupesh et al, 2011b). Cre-mediated fate-mapping analysis reveals the complexity of the origins for the LA, BLA and BMA nuclei (Waclaw et al, 2010).…”
Section: Pax6mentioning
confidence: 99%
“…The projection neurons in the excitatory LA and BLA nuclei are derived from the VP and LP (Stenman et al, 2003;Puelles et al, 2000;Hirata et al, 2009). Neurons in the central and medial extended amygdala are originated from multiple telencephalic or extra-telencephalic progenitor zones (Bupesh et al, 2011a;Bupesh et al, 2011b). Cre-mediated fate-mapping analysis reveals the complexity of the origins for the LA, BLA and BMA nuclei (Waclaw et al, 2010).…”
Section: Pax6mentioning
confidence: 99%
“…3 d of Rodríguez-Moldes, 2009]. Although the ventricular zone of the pallium appears to be the potential source for these Pax6 cells, more studies are needed to know if this is the only source, as reported in Xenopus [Moreno et al, 2008], or if they may derive in part from the dorsal subdivision of the LGE, as reported in amniotes [Puelles et al, 2000;Flames et al, 2007;Abellán and Medina, 2009;Moreno et al, 2010;Bupesh et al, 2011;Medina et al, 2011]. Whatever its origin, this stream of Pax6 cells may be a useful landmark in Scyliorhinus of the lateral margin of the LGE equivalent (developing striatum).…”
Section: Gad/pax6mentioning
confidence: 99%
“…4 l) points to its probable pallial origin. However, other possible sources must also be considered, as it is known that in amniotes the amygdala receives Pax6-expressing cells from outside the telencephalon, including the thalamic eminence [Abellán and Medina, 2009;Bupesh et al, 2011]. This could be also possible in S. canicula , where the thalamic eminence also contains Pax6 cells [Rodríguez-Moldes, 2009] and a stream of these cells appears to extend between this diencephalic region and the amygdala-like subpallial region (open arrow in fig.…”
Section: Stage-32 Embryosmentioning
confidence: 99%
“…In the mouse, the LGE appears to show a dorsal subdivision characterized by production of postmitotic cells expressing Pax6, and a ventral subdivision characterized by expression of Islet1 in the subventricular zone and mantle [Puelles et al, 2000;Stenman et al, 2003;Flames et al, 2007]. Based on the expression of Pax6 and fate mapping, it appears that many neurons of the central amygdala originate in the dorsal LGE [Puelles et al, 2000;Bupesh et al, 2011b], and this appears to be true for the intercalated cells as well [Kaoru et al, 2010]. On the other hand, based on a genetic fate map of Islet1, many neurons of the central amygdala also originate in the ventral LGE [Waclaw et al, 2010;Bupesh et al, 2011b].…”
Section: Development and Evolution Of The Amygdalamentioning
confidence: 99%
“…Based on the expression of Pax6 and fate mapping, it appears that many neurons of the central amygdala originate in the dorsal LGE [Puelles et al, 2000;Bupesh et al, 2011b], and this appears to be true for the intercalated cells as well [Kaoru et al, 2010]. On the other hand, based on a genetic fate map of Islet1, many neurons of the central amygdala also originate in the ventral LGE [Waclaw et al, 2010;Bupesh et al, 2011b]. Central and intercalated nuclei of the amygdala are involved in the control of ingestion and fear responses by way of projections to specific nuclei of the hypothalamus and brainstem [Swanson, 2000;Paré et al, 2004].…”
Section: Development and Evolution Of The Amygdalamentioning
confidence: 99%